BUDAYA POLITIK GENERASI MILENIAL: IDEOLOGIS ATAU APATIS? - Indrawan, Jerry (UIN Alauddin Makassar, 2025)
The millennial generation, also known as generations Y and Z, is a group that is highly taken into account in modern political contestation. This generation is believed to be able to determine the outcome of a general election because they are in the majority. However, the potential for the millennial generation not to want to be involved in politics, let alone vote in elections, is also large. This is because they have high exposure to information technology, but do not have adequate political literacy. As a result, they do not have an ideological political culture, which is based on Pancasila, for the benefit of the nation and state. Thus, this generation's tendency to become apathetic is high. Through qualitative research methods, the author will discuss whether the millennial generation really has no interest in politics or can be said to be apathetic or whether they actually still have an ideological political culture. Data collection was carried out secondaryly through literature studies using books, scientific journals and online news sites.